An analytical study of photoacoustic and thermoacoustic generation efficiency towards contrast agent and film design optimization - Gao, Fei (2018)
Photoacoustic (PA) and thermoacoustic (TA) effects have been explored in many applications, such as bio-imaging, laser-induced ultrasound generator, and sensitive electromagnetic (EM) wave film sensor. In this paper, we propose a compact analytical PA/TA generation model to incorporate EM, thermal and mechanical parameters, etc. From the derived analytical model, both intuitive predictions and quantitative simulations are performed. It shows that beyond the EM absorption improvement, there are many other physical parameters that deserve careful consideration when designing contrast agents or film composites, followed by simulation study. Lastly, several sets of experimental results are presented to prove the feasibility of the proposed analytical model. Overall, the proposed compact model could work as a clear guidance and predication for improved PA/TA contrast agents and film generator/sensor designs in the domain area.